Elevating reading skill with spinning wheel media at MTsN 2 Muaro Bungo - Renni Hasibuan; Nabila Fakhrunnisa (Institut Agama Islam Negeri Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
The use of media in the learning process is crucial as it can enhance student engagement, facilitate material comprehension, and create interactive and engaging learning experiences. Therefore, this study aims to measure the effectiveness of using a spinning wheel media in improving the reading skills of students at MTsN 2 Muaro Bungo. This research employs a quantitative approach utilizing a quasi-experimental design. Data collection procedures involve administering pretests and posttests to both control and experimental groups. The collected data are then analyzed using descriptive statistical tests, assessments for data normality using the Kolmogorov-Smirnov test, and independent t-tests. The results of the study indicate that the use of spinning wheel media has a significantly positive impact on enhancing students' reading abilities. The significant difference test results demonstrate a strong statistical disparity between the group using spinning wheel media and the control group without using this media in reading skill learning. Therefore, this research provides valuable insights for educators and educational institutions to consider integrating spinning wheel media into Arabic language teaching strategies to enhance the overall quality and outcomes of student learning.